Back Cover: Encapsulation of Metalloporphyrins in a Self‐Assembled Cubic M8L6 Cage: A New Molecular Flask for Cobalt–Porphyrin‐Catalysed Radical‐Type Reactions (Chem. Eur. J. 31/2013). Issue 31 (19th July 2013) - Otte, Matthias; Kuijpers, Petrus F.; Troeppner, Oliver; Ivanović‐Burmazović, Ivana; Reek, Joost N. H.; de Bruin, Bas
<x xml:space="preserve">Abstract</x> Radicals caged in a cube! A new, large cubic M8L6 host capable of encapsulating a catalytically active metalloradical‐type cobalt–porphyrin catalyst is described by de Bruin and co‐workers in their Full Paper on page 10170 ff. The reactions mediated by this system are the first examples of cobalt–porphyrin‐catalyzed radical‐type transformations involving diazo compounds that occur inside a supramolecular cage. The cover is an artistic impression of their work in the typical cubistic style of the Dutch painter Piet Mondriaan.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>